(untitled) (Andamios, Revista de Investigación Social, 2013)
This article debates the relevance of the diverse theories of modernity. The text analyzes the theories of the modernity of last 40 years (postmodern, reflexive modernity, liquid modernity, multiple modernities and entangled modernities) and proposes that the analogical hermeneutics helps to solve the dispute. Opposite to the speeches of a uniform and univocal modernity or of a theory of the modernity totally relativistic, this study proposes an analogical modernity that recovers a minimum of common concepts that make possible processes of appropriation and recovery of the categories, practices and institutions of the modernity.